2016
DOI: 10.1134/s1990750816010029
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity and pathogenetic targets for seaweed sulfated polysaccharides in herpesvirus infections

Abstract: The review summarizes results of studies of effects of sulfated polysaccharides from seaweed on herpesviruses and the course of herpesvirus infections. Importance of this problem is determined by the prev alence of herpesviruses that can persist in the human body and demonstrate a high degree of immune mimicry and resistance to antiviral drugs. A wide range of physiological action of sulfated polysaccharides, receptor agonists of innate and adaptive immune cells, which possess potent antiviral, antioxidant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…This result suggests the capability of these SPs to avoid viral adsorption to the cell; these data were confirmed by viral penetration assays where we observed less antiviral activity after viral attachment to the cell. More recent studies have demonstrated that fucoidans exhibit their antiviral activity when the compound is present during the virus adsorption period by blocking the interaction of viruses to the cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests the capability of these SPs to avoid viral adsorption to the cell; these data were confirmed by viral penetration assays where we observed less antiviral activity after viral attachment to the cell. More recent studies have demonstrated that fucoidans exhibit their antiviral activity when the compound is present during the virus adsorption period by blocking the interaction of viruses to the cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of SSPS on viral replication in vitro have been known for more than 60 years with activities against several enveloped RNA viruses, the family of the current source of pandemic SARS-CoV-2, such as HIV (various strains), Sindbis, Semliki forest, Junin, Tacaribe, VSV, Influenza A, and RSV viruses ( Luescher-Mattli, 2003 ; Pujol et al, 2007 ; Witvrouw & De Clercq, 1997 ; Gerber et al, 1958 ; Chiu et al, 2012 ; Hayashi, Hamada & Hayashi, 1996 ; Lee et al, 2004 ; Besednova et al, 2016 ; Terasawa et al, 2020 ). As an example, SSPS was found to block HIV replication in cell cultures, at concentrations as low as 10 µg mL −1 and without showing any toxicity to the host cells at concentrations of up to 2.5 mg mL −1 ( Luescher-Mattli, 2003 ; Witvrouw & De Clercq, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral properties of sulfated polysaccharides are highly dependent on the presence of sulfate ester groups, where the higher the DS, the better the antiviral potency [112,113]. Sulfated polysaccharides with high average molecular weight generally display better antiviral properties than those with low average molecular weight.…”
Section: Antiviral Fucoidanmentioning
confidence: 99%
“…Low molecular weight sulfated polysaccharides can possess strong antiviral properties though, especially when the DS is high [113]. Although fucoidan exhibit antiviral properties both in vitro and in vivo, they have shown no direct (or on a few occasions very weak) virucidal activity [1,112,114].…”
Section: Antiviral Fucoidanmentioning
confidence: 99%
See 1 more Smart Citation